Enantiomeric 3-arylcoumarins and 2-arylcoumarones from the roots of Glycyrrhiza uralensis as protein tyrosine phosphatase 1B (PTP1B) inhibitors1. Issue 56 (19th June 2015) - Ji, Shuai; Qiao, Xue; Li, Zi-wei; Wang, Yong-rui; Yu, Si-wang; Liang, Wen-fei; Lin, Xiong-hao; Ye, Min
<x xml:space="preserve">Abstract</x> Four new PTP1B inhibitors were isolated from Glycyrrhiza uralensis, and the absolute configuration of 2, 3-dihydro-2, 3, 3-trimethylbenzofurans was first unambiguously established.